Successful treatment of an adult with Kasabach-Merritt syndrome using thalidomide, vincristine, and prednisone. Issue 4 (April 2019) - Huang, Yue-Hua; Zhou, Dao-Bin; Han, Bing; Li, Tian; Wang, Shu-Jie
Objective: Kasabach-Merritt syndrome is a rare disease that mainly occurs in infants and adolescents. It usually manifests as disseminated intravascular coagulation and severe bleeding, and is associated with high mortality. However, its low incidence and clinical rarity in adults mean that there is currently no well-verified treatment regimen for this disease. We report on an effective novel therapeutic regimen in a patient with Kasabach-Merritt syndrome. Methods: A woman with Kasabach-Merritt syndrome presented with a recurrent subcutaneous mass and disseminated intravascular coagulation, and was treated with prednisone, vincristine and thalidomide. Results: This treatment regimen successfully resolved the patient's symptoms, with tumor regression. The patient remained disease-free after 6 years of follow-up. Conclusions: Prednisone combined with vincristine and thalidomide may be an effective treatment for Kasabach-Merritt syndrome, but further studies are needed to verify the use of this regimen.